Determination of the Lipophilicity of Ibuprofen, Naproxen, Ketoprofen, and Flurbiprofen with Thin-Layer Chromatography - Andrzej Czyrski (Journal of Chemistry)
The lipophilicity is an important parameter that influences the activity of the drugs in the human body. The reversed phase high performance thin layer chromatography was applied to determine the Log P values of ibuprofen, ketoprofen, naproxen, and flurbiprofen. The stationary phase used in the study was silica-gel coated plates. The mobile phase was the mixture of acetonitrile and water in different proportions. The content of acetonitrile varied in 5% increments from 50% to 80%. The Rm0 values were determined for the compounds with a known Log P and for the analyzed substances (ibuprofen, naproxen, ketoprofen, and flurbiprofen). The Log P values were calculated for the analyzed compounds using the regression curve Rm0 = f(Log P) parameters for the compounds with the known lipophilicity. Flurbiprofen is characterized by the highest Log P value: 3.82. The lowest one is noted for ketoprofen: 2.66. The determined Log P values of tested compounds were similar to the values calculated by the software.